Green Curriculum: Sustainable Learning at a Higher Education Institution - Louw, Willa (International Review of Research in Open and Distributed Learning, 2013)
The United Nations (UN) constituted 2005–2014 as the decade for educational sustainable development when bridges have to be built between academic institutions and their communities. In this article I will therefore do a literature search from 2005–2011 on what it means to be a sustainable university with a sustainable curriculum by looking at case studies from other higher education institutions in order to begin to give guidelines for such an endeavour in an open and distance learning (ODL) institution. Thereafter I will focus on recommendations on how to transform present study material into a green curriculum by using a qualification in Human Settlements as a case study.